2014
DOI: 10.1038/jid.2013.286
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–Pituitary–Thyroid Axis Hormones Stimulate Mitochondrial Function and Biogenesis in Human Hair Follicles

Abstract: Thyroid hormones regulate mitochondrial function. As other hypothalamic-pituitary-thyroid (HPT) axis hormones, i.e., thyrotropin-releasing hormone (TRH) and thyrotropin (TSH), are expressed in human hair follicles (HFs) and regulate mitochondrial function in human epidermis, we investigated in organ-cultured human scalp HFs whether TRH (30 nM), TSH (10 mU ml(-1)), thyroxine (T4) (100 nM), and triiodothyronine (T3) (100 pM) alter intrafollicular mitochondrial energy metabolism. All HPT-axis members increased ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 80 publications
(101 reference statements)
6
102
0
Order By: Relevance
“…The mitochondrial data here presented suggest that THs stimulate intraepidermal mitochondrial biogenesis (Supplementary Figure S3) as they do in many other tissues, including human hair follicles (Cioffi et al, 2013;Lee et al, 2012;Marin-Garcia, 2010;Santillo et al, 2013;Vakitus et al, 2015;Vidali et al, 2014), via a sirt1-PGC1α-mediated pathway. Also, both THs decreased mTORC1/2, whose inhibition is involved in mitochondrial biogenesis and reportedly restores a more juvenile phenotype and increased life span (Chiao et al, 2016;Evangelisti et al, 2016;Johnson et al, 2013).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The mitochondrial data here presented suggest that THs stimulate intraepidermal mitochondrial biogenesis (Supplementary Figure S3) as they do in many other tissues, including human hair follicles (Cioffi et al, 2013;Lee et al, 2012;Marin-Garcia, 2010;Santillo et al, 2013;Vakitus et al, 2015;Vidali et al, 2014), via a sirt1-PGC1α-mediated pathway. Also, both THs decreased mTORC1/2, whose inhibition is involved in mitochondrial biogenesis and reportedly restores a more juvenile phenotype and increased life span (Chiao et al, 2016;Evangelisti et al, 2016;Johnson et al, 2013).…”
Section: Discussionsupporting
confidence: 51%
“…As the latter is difficult to assess in tissue sections, this was examined in cultured primary human epidermal keratinocytes (NHEK), using a ROS-specific dye (CM-H2DCFDA) (Vidali et al, 2014). This showed that treatment with different concentrations of either T 3 (50, 100 and 200 pM) or T 4 (50, 100 and 200 nM) for 24 hours failed to increase ROS production (Supplementary Figure S6).…”
Section: Ths Do Not Up-regulate Ros Production In Human Epidermal Kermentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroxin has a strong polyfunctional action: it increases basal metabolism (Alva-Sánchez et al, 2012), activates mitochondrial function (Vidali et al, 2014), changes water and mineral metabolism (Reddy On the axes: 1 -mitochondrial respiratory control; 2 -content of TBARS in microsomal fractions; 3 -the rate of generation of superoxide radical in microsomal fractions; 4 -content of TBARS in the mitochondrial fraction; 5 -malate dehydrogenase activity; 6 -the rate of generation of free radicals in the mitochondrial fraction; 7 -rate of oxygen consumption in state V2; 8 -rate of oxygen consumption in state V3; 9 -glutathione reductase activity; 10 -glutathione peroxidase activity; 11 -activity of isocitrate dehydrogenase; 12 -activity of glutathione-S-transferase. et al, 2012), increases mitochondrial membrane permeability (Maity et al, 2013), and activates transcription of several genes (Yap et al, 2013) and can regulate other cell functions.…”
Section: Enzymesmentioning
confidence: 99%